A Nonessential Signal Peptidase II (Lsp) of Myxococcus xanthus Might Be Involved in Biosynthesis of the Polyketide Antibiotic TA - Paitan, Yossi (American Society for Microbiology, 1999)
Myxococcus xanthus is a gram-negative soil bacterium that produces the polyketide antibiotic TA. In this study, we describe the analysis of an M. xanthus gene which encodes a homologue of the prolipoprotein signal peptidase II (SPase II; lsp). Overexpression of the M. xanthus SPase II in Escherichia coli confers high levels of globomycin resistance, confirming its function as an SPase II. The M. xanthus gene encoding the lsp homologue is nonessential for growth, as determined by specific gene disruption. It has been mapped to the antibiotic TA gene cluster, and the disrupted mutants do not produce the antibiotic, indicating a probable involvement in TA production. These results suggest the existence of more than one SPase II protein in M. xanthus, where one is a system-specific SPase II (for TA biosynthesis).